Financial Soundness of Maharatna Companies: Application of Altman Z Score Model - Chitta, Shyamsunder; Jain, Ravi Kumar; Sriharsha, R. (Indian Journal of Finance, 2019)
Maharatna companies are the top most PSUs contributing greatly to the development of our nation and have existed for a long time and became self-sustained without depending on the government for funds. Recently, some of the companies have started losing profits continuously and are on the verge of bankruptcy. The government has been infusing funds to safeguard them, but is not able to improve their performance to the desired level. The purpose of this paper was to study the financial situation of eight Maharatna companies by applying the famous Altman Z score model to verify whether these companies really suffered financially during the period from 2014 to 2018. It was found that not all the Maharatna companies were performing as expected.